The untamed God : a philosophical exploration of divine perfection, immutability, and simplicity - Richards, Jay W. (Jay Wesley), 1967- (Downers Grove, Illinois, InterVarsity Press, 2003)
The essential tenets of classical theism regarding the doctrine of God can be stated fairly easily. However, questions have been raised regarding the coherence of these beliefs taken as a whole. Some have seen fit to abandon classical theism. Others have acknowledged tensions in the traditional concept of God and have sought to resolve them by means of making significant concessions. Jay Wesley Richards believes that classical theism with its biblical norm can and ought to be maintained. He shows how a philosophical defense, using the analytical tools of modal logic, can be mounted that preserves traditional Christian beliefs. Richards astutely defends essentialism, arguing that it is both intrinsic to the Christian understanding of God and preserves the contingency of creation and the God-world relation. To further clarify and defend his proposal he engages appreciatively and critically the thought of Karl Barth and Charles Hartshorne as well as addressing the related and currently debated matters of divine simplicity and immutability.
Christian theism : some preliminary issues -- From modal speech to essentialism -- Theological essentialism -- Karl Barth's actualistic doctrine of God -- Dealing with Barth's doctrine of God -- Charles Hartshorne's surrelativist doctrine of God -- Dealing with Hartshorne's doctrine of God -- The difficult doctrine of divine immutability -- The difficult doctrine of divine simplicity.
Includes bibliographical references (pages 251-261) and indexes.
Keywords: God -- Attributes; Essentialism (Philosophy); Philosophical theology; Christianity -- Philosophy